2015
DOI: 10.2106/jbjs.m.01327
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Bearing-Line Analysis in Supramalleolar Osteotomy for Varus-Type Osteoarthritis of the Ankle

Abstract: Traditional tibial correction resulted in great variation in the locations of the postoperative mechanical ankle joint axis point. In ankles with the preoperative point more medial than the tibial plafond, the point was insufficiently moved to the lateral side, and the clinical outcomes were less satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 16 publications
2
80
0
Order By: Relevance
“…Additionally, Kim et al [11] reported that no radiological outcome seemed to have a significant influence on the clinical outcomes. We agree with Mann et al [18] that realignment surgery of the ankle joint with osteotomy is worthwhile, even for high TT patients, because the osteotomy will redistribute the contact forces of the ankle joint and move the mechanical axis point of the ankle laterally [13], prolong the viability of a more normally aligned joint, and even restore the TT to a neutral position (Fig. 6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, Kim et al [11] reported that no radiological outcome seemed to have a significant influence on the clinical outcomes. We agree with Mann et al [18] that realignment surgery of the ankle joint with osteotomy is worthwhile, even for high TT patients, because the osteotomy will redistribute the contact forces of the ankle joint and move the mechanical axis point of the ankle laterally [13], prolong the viability of a more normally aligned joint, and even restore the TT to a neutral position (Fig. 6).…”
Section: Discussionsupporting
confidence: 91%
“…Other limitations included that we only used the Maryland foot score for functional evaluations and that the pre- and postoperative radiological evaluations did not include the weight-bearing full leg anterior-posterior view, which would be useful for the full leg alignment evaluation. Haraguchi et al [13] used hip-to-calcaneus radiographs to evaluate lower limb alignment in SMOT patients and reported that when the preoperative mechanical axis point was more medial than the tibial plafond, the point was insufficiently moved to the lateral side, and the clinical outcomes were less satisfactory. This finding is important for preoperative evaluations and selecting the proper operation for mid-stage varus ankle OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The talar tilt angle was completely corrected postoperatively (from 14.5 to 1.2 degrees), and the tibiocrural angle also was well corrected. ‡References 1,3,4,7,8,10,[12][13][14][15][18][19][20]24,26,27. …”
mentioning
confidence: 99%
“…Supramalleolar osteotomy (SMOT) is an effective procedure for the treatment of midstage asymmetric ankle osteoarthritis [1][2][3][4]. Related studies have proved that the key factors affecting the postoperative curative effect of SMOT are the postoperative ankle Takakura stage [5], lower limb power line [6] and ankle angles [7]; but SMOT uses conventional operation (CO) method often does not perfectly accomplish these surgical aims leading to some patients have unsatisfactory outcomes [8,9]. The reasons include preoperative planning dependence on freehand drawing, and surgeons determine the operative procedure all depend on the surgeon's experiences and fluoroscopies [10].…”
Section: Introductionmentioning
confidence: 99%